Abnormal plasma neuroactive progestagen derivatives in ill, neonatal foals presented to the neonatal intensive care unit. (22nd April 2013) - Aleman, M.; Pickles, K. J.; Conley, A. J.; Stanley, S.; Haggett, E.; Toth, B.; Madigan, J. E.
Summary Reasons for performing the study Increased levels of pregnanes have been reported in foals with neonatal maladjustment syndrome (NMS). These steroids may cross the blood–brain barrier and have depressive effects in the central nervous system leading to behavioural abnormalities and altered states of consciousness in affected foals. Objectives The aim of this study was to determine the pregnane profile of foals with NMS and compare it with that of healthy controls and sick, non‐NMS foals. Study design Prospective‐clinical study. Methods Thirty‐two foals with a clinical diagnosis of NMS, 12 foals with other neonatal disorders and 10 healthy control foals were selected for the study. Heparinised blood samples were collected from each group of foals and pregnane and androgen concentrations determined using liquid chromatography mass spectrometry at 0, 24 and 48 h of age. Results Healthy foals showed a significant decrease in pregnane concentrations over the first 48 h of life (P<0.01). Foals with NMS and sick, non‐NMS foals had significantly increased progesterone, pregnenolone, androstenedione, dehydroepiandrosterone and epitestosterone concentrations compared with healthy foals (P<0.05). Progesterone and pregnenolone concentrations of sick, non‐NMS foals decreased significantly over 48 h (P<0.05), whereas concentrations in NMS foals remained increased. Conclusions and potential relevance Pregnane concentrations of ill, neonatal foals remain increased following birth, reflecting a delayed, or interrupted, transition from intra‐ to extra‐uterine life. Serial progesterone and pregnenolone measurement may be useful in aiding diagnosis of NMS.